Impact of an AlGaN spike in the buffer in 0.15 μm AlGaN/GaN HEMTs during step stress. (November 2021) - Gao, Zhan; Rampazzo, Fabiana; Meneghini, Matteo; Modolo, Nicola; De Santi, Carlo; Blanck, Hervé; Stieglauer, Hermann; Sommer, Daniel; Grünenpütt, Jan; Kordina, Olof; Chen, Jr-Tai; Jacquet, J-C; et al.
Abstract: On-wafer robustness and short-term reliability of 0.15 μm AlGaN/GaN HEMTs, fabricated on AlGaN buffer with a 'mono-layer' and c backbarrier between channel and buffer layers, have been compared. Results of DC characterization showed that devices with AlGaN 'bi-layer' backbarrier have better subthreshold behaviour, reduced on-resistance and leakage current, together with a slightly lower current and transconductance. Electroluminescence measurements suggested an increase of electric field in the 'bi-layer' devices. Observed failure modes are the following: (a) during off-state stress, threshold voltage shifts towards more negative values; (b) for semi-on and on-state tests, a non-monotonic threshold voltage instability, which initially becomes negative and then recovers is common to both types of devices; (c) during semi-on and on-state tests, a significant increase of RON occurs, which seems to be faster in devices without spike, despite the lower electric field suggested by EL measurements. Degradation of electrical characteristics has been attributed to the instability of charge on Carbon-related acceptor levels, enhanced by hot-electron effects.